(untitled) (Cadernos de Sociomuseologia, 2025)
This article seeks to map social markers through the slave trade in the periodical “Idade d’Ouro do Brazil” (Golden Age of Brazil), from the city of Salvador, Bahia, using the search service of the Brazilian Digital Newspaper Library, which belongs to the Online Archive of the National Library, and relate them to intersectionality and its implications for education on ethnic-racial relations. As a contribution, references are sought in the bibliography to briefly understand the concept of intersectionality, define the most striking social markers in relation to the education of ethnic-racial relations, and thus illustrate this first through the newspaper’s advertisements for the purchase and sale of slaves in order to understand how the slave trade was established. This emphasizes the characteristics of the slaves who were normally bought and sold, as well as how these slaves were advertised. The results of the research provide a brief overview of the activities of slaves, their age, gender, and other specificities that mark the social subject through the perspective of intersectionality, relating to the current meanings of African descent. Keywords: Trade. Enslaved people. Social markers. Intersectionality.